Operative instruments to support public authorities and industries for the supply of raw materials: A decision support tool to evaluate the sustainable exploitation of extractive waste facilities. (March 2023) - Mancini, Susanna; Casale, Marco; Rossi, Piercarlo; Faraudello, Alessandra; Dino, Giovanna Antonella
Abstract: The need to guarantee access to raw materials (RM) has stimulated EU policies to find alternative and integrative sources to exploit. RM can be recovered from anthropogenic deposits and from productive cycles, applying respectively landfill mining and circular economy approaches. In order to assess, quickly, whether extractive waste facilities prove to be sufficiently rich to become potentially exploitable, the use of a Decision Support Tool (DST) is presented here. This tool investigates waste facilities both with quantitative (technical and economic) and qualitative (social and environmental) data. The outputs of the DST are represented by several possible scenarios, useful to decide if and how to approach extractive waste exploitation. After working on the structure of the DST, the produced support instrument has been tested and validated using data and processing flow chart of 3 real case studies: the one of Gorno (Zn–Pb) mining site is presented here. Graphical abstract: Image 1 Highlights: Presence of resources in anthropogenic deposits (i.e. extractive waste facilities). Sustainable RM/CRM exploitation from extractive waste (EW) facilities. Decision Support Tool (DST) to guarantee multidisciplinary approach in managing EW. DST-EW as an instruments to help decision makers in programming RM (and CRM) supply. Evaluation of multiple scenarios considering social, economic, environmental aspects.